Analisis Pesan - Purwasito, Andrik (Jurnal The Messenger, 2017)
In today's contemporary life, information scattered innumerable quantity, either spread through electronic media, printable media and via the internet. Such information is not all give hope of a better life, but rather a flood of false information/lies (a hoax). Every day we look at the discourse is growing increasingly wild and hard to believe. News sources are now numberless. In the face of information with the meaning that is not valid, distorted facts, lie packed with goodness, then the public is also often victims of the information. Communicators, Participants, both Agency and Structure, becoming a multi-sources. Difficult to determine the source is credible. To become a critical public, the authors offer an analysis of the message, which allows readers to practice in both research thesis and dissertation as well as to simply be able to avoid the falsehoods and lies of information.